The review of virtual and visual experience / Nabilah Abdul Wahab - Abdul Wahab, Nabilah (Faculty of Health Sciences, 2015)
The increasing rate of road crashes in this newly era had opened space of research to be conducted virtually. Hence, this study primarily designed to define the concept of virtual and visual experience. The understanding of this knowledge then enables the comparison of its application to be analyzed, especially in the field of engineering, medical and psychological. Numerous studies were reviewed involving the virtual and visual experience, which was related to the subject's state of consciousness and awareness, ability to control the task given as well as the visual condition. These related studies were compared and interpreted accordingly, while those studies that were not associated with this review were eliminated. The results of the study indicated that the usage of virtual and visual experience in research had contributed to many fields that benefits humanity and reduce the risk of injuries and crashes more, including cost saving. Yet, the studies often linked to the effects where the subjects might feel motion sickness as the inability of the instrument to produce enough motion exposure during the research process. Moreover, most studies showed the driving impairment and road accidents in subjects that has a visual impairment. Thus, this study proposed that, the good visual requirements were important and crucial in each driver as even the task performed in virtual by visually impaired drivers proven to be unsafe. In future, the studies on proper visual needs for driving compatibility are needed to address certain benchmark for safe driving practice.